Talking to my daughter a brief history of capitalism - Varoufakis, Yanis (London Vintage, 2019)
In this letter to his teenage daughter, one of the world's most famous economists uses vivid stories to explain what economics is and why it is so dangerous. What is money and why does debt exist? Where do wealth and inequality come from? How come economics has the power to shape and destroy our lives? Economics is not a technical science, it is an epic drama: a battleground of ideas, a war between the powerful for our allegiance. In this universally accessible book, Yanis Varoufakis describes how this drama first emerged and has since come to dominate the fate of human societies worldwide. In answering all of the big questions about money and debt, power and inequality, he shows how economics has sought to solve the problems of our world but ended up being a major cause of many of them. Drawing on history and literature, science fiction and personal memories, this intimate and inspiring book shines a light for readers of all ages on some of the most bewildering questions and important challenges that humanity faces
Includes index
Keywords: Economics